Preparação e caracterização óptica de filmes de poli(estireno sulfonados) dopados com neodímio - Cristovan,Fernando H. (2005)
In this work we describe the processing of poly(styrene sulphonate) films (PSS) doped with neodymium (Nd). Optical density measurements in the UV-Vis-NIR region show the typical bands observed for neodymium chloride (NdCl3) in solution. In the case of films, the intensity ratio between the peaks at 800 nm (4I9/2 -> 4F5/2 + ²H7/2) and 580 nm (4I9/2 -> 4G5/2 + ²G7/2) is equal to 0.83. Infrared spectra present an enhancement in the absorption region of aromatic rings. Site selective luminescence spectroscopy shows that the incorporation of Nd introduces a hipsochromic shift and a line shape definition in UV luminescence compared to PSS film, decreasing the interaction between aromatic groups. In addition, the film exhibits an intense radiative transition at 1061 nm (4F3/2->4I11/2), comparable to the one present in crystalline materials doped with Nd.